2017
DOI: 10.1080/16549716.2017.1290916
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of second-line antiretroviral treatment in an adult and adolescent cohort in Myanmar

Abstract: Background: Myanmar has a high burden of Human Immunodeficiency Virus (HIV) and second-line antiretroviral treatment (ART) has been available since 2008 in the public health sector. However, there have been no published data about the outcomes of such patients until now.Objective: To assess the treatment and programmatic outcomes and factors associated with unfavorable outcomes (treatment failure, death and loss to follow-up from care) among people living with HIV (aged ≥ 10 years) receiving protease inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 22 publications
6
21
0
Order By: Relevance
“…The overall incidence of second-line treatment failure in this study was similar with studies conducted in African and Asian countries [ 18 20 ]. However, the incidence of the treatment failure of this study was lower as compared to the study conducted in South Africa, other studies from African and Asian patients, Amhara region, Ethiopia (9.86 per 100 PYs) and systematic analysis (15.0 per 100 PYs) [ 17 , 21 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…The overall incidence of second-line treatment failure in this study was similar with studies conducted in African and Asian countries [ 18 20 ]. However, the incidence of the treatment failure of this study was lower as compared to the study conducted in South Africa, other studies from African and Asian patients, Amhara region, Ethiopia (9.86 per 100 PYs) and systematic analysis (15.0 per 100 PYs) [ 17 , 21 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…Another comparatively higher rate of virological failure of 17.7% was reported in India among patients who were on second line ART beyond 1 year [12] and in South Africa where it was shown that about 23% of patients who failed on first line ART experienced virological failure after 1 year of treatment with second line ART [11]. A much higher rate of virological failure of 37% was also recently reported from Myanmar Asia among patient who were on second line ART [22].…”
Section: Discussionmentioning
confidence: 90%
“…First-line led to longer life expectancy (28.8 years) and lower life time costs ($41,350/person, from lower second-line costs) [14]. Some studies also showed that the occurrence of un- favorable outcome as death, lost to follow up and virologic failure occurs at rate of 7.9 patients per 100 person years follow-up in patients on second line ART regimens [15]. Many research also revealed that early mortality, drug toxicity and resistance is high in second line ART [16].…”
Section: Introductionmentioning
confidence: 99%